Perancangan Alat Pencetak Baso Efektif Yang Terbuat Dari Paralon - Dhiya Kamalugin; Gugup Tugi Prihatma; Ahmad Nalhadi; M Bob Anthony; Rosihin Rosihin (Jurnal Inovasi dan Kreativitas (JIKa), 2023)
Problems: Forced bakso making in a family neighborhood when you want to make a bakso is to go to a grinding place with a mixture that has to follow the grinder can not suit the taste of a household that allows its own mixture and then back home to print with a manual hand that is quite time-consuming on the journey from market to home that maybe a meat grinder does not necessarily exist in all traditional markets. Then it is necessary to simplify the time by making it all possible to do at one point. It is not necessary to go to a place that can do the grinding and mixing of the dough. Purpose: The purpose of this study is to find out the timing of the process of making a printing tool. Methodology: The method used is the stopwatch method, this method is done by measuring time through observation and recording the working times for each cycle using the tools that have been prepared for which time data is then calculated in real time. Results/Findings: The results of this study showed the calculation of raw time using the stop-hour method of the long raw time required in the process of manufacture of a base printer 12.67 minutes. The duration of the raw time is obtained from the cumulative raw time of each work operation undertaken at the time of manufaction of the base printers. Paper Type: research